2008
DOI: 10.4049/jimmunol.180.5.3366
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Antimicrobial Proteins S100A8 and S100A9 Inhibits Phagocyte Migration to the Alveoli in Streptococcal Pneumonia

Abstract: We investigated the roles of the potent, chemotactic antimicrobial proteins S100A8, S100A9, and S100A8/A9 in leukocyte migration in a model of streptococcal pneumonia. We first observed differential secretion of S100A8, S100A9, and S100A8/A9 that preceded neutrophil recruitment. This is partially explained by the expression of S100A8 and S100A9 proteins by pneumocytes in the early phase of Streptococcus pneumoniae infection. Pretreatment of mice with anti-S100A8 and anti-S100A9 Abs, alone or in combination had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 46 publications
9
118
2
1
Order By: Relevance
“…Bacteria are thought to contain high-affinity zinc transporters as a strategy to overcome zinc limitation during infection in which the acute phase response has been shown to result in reduced plasma zinc concentrations (20,38) with upregulation and release of the zinc binding complex calprotectin in the blood and lungs (29,31,55). In accord with this hypothesis, we demonstrated here that H. influenzae requires a specialized high-affinity zinc utilization pathway for virulence.…”
Section: Discussionsupporting
confidence: 76%
“…Bacteria are thought to contain high-affinity zinc transporters as a strategy to overcome zinc limitation during infection in which the acute phase response has been shown to result in reduced plasma zinc concentrations (20,38) with upregulation and release of the zinc binding complex calprotectin in the blood and lungs (29,31,55). In accord with this hypothesis, we demonstrated here that H. influenzae requires a specialized high-affinity zinc utilization pathway for virulence.…”
Section: Discussionsupporting
confidence: 76%
“…Although gene knockout of S100A8 resulted in embryonic lethality (Passey et al, 1999) and information on that of SAA3 is currently not available, TLR4-deficient mice displayed an organ-specific disorder, pulmonary emphysema (Zhang et al, 2006). Inhibition of S100A8 abrogated myeloid cell infiltration into pneumonic lungs that requires transendothelial and transepithelial cell migration to reach the pathogens (Kerkhoff et al, 1999;Ryckman et al, 2003;Vogl et al, 2004;Raquil et al, 2008). Bacteriocidal reactive oxygen species production is regulated by the interaction of S100A8 and cofactors of Nox2, such as p67 and Rac2 (Kerkhoff et al, 2005) or a direct binding between TLR4 and Nox4 (Park et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although S100A8 induced another TLR4 agonist serum amyloid A3 (SAA3) in pulmonary macrophages and endothelial cells (Hiratsuka et al, 2008), it was also shown by other groups that TNFa can induce SAA3 expression in granulosa cells (Son et al, 2004) and nuclear factor-kB binds enhancer factor for SAA3 (Bing et al, 2000). S100A8 appears to have a homeostatic role in pulmonary defense against microbes because S100A8 promotes leukocyte chemotaxis in lungs (Ryckman et al, 2003) and transendothelial as well as transepithelial migration of leukocytes are impaired by inhibition of S100A8 (Raquil et al, 2008;Vogl et al, 2004). Another proposed receptor for S100A8 is glycan-linked RAGE (receptor for advanced glycation endproducts) (Turovskaya et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
“…An anti-S100A8 blocking antibody abrogated transepithelial migration of macrophages and neutrophils into the alveolar space. 48 In addition, S100A8 is capable of inducing NOS2, 49 and TLR4 signaling is closely linked with ROS generation. [50][51][52] Thus, endogenous ligand may serve to balance TLR4-mediated NF-kB signaling that is sensitive to redox.…”
Section: The Concept Of Homeostatic Inflammation Explains the Premetamentioning
confidence: 99%